2021
DOI: 10.24940/theijhss/2021/v9/i3/hs2103-020
|View full text |Cite
|
Sign up to set email alerts
|

The Practices of Traditional knowledge and Wisdom by Multi-Ethnics on Swidden Agriculture of Kalimantan, Indonesia

Abstract: Traditional Indigenous knowledge can be defined as a networkof knowledges, beliefs, and traditions intendedto preserve, communicate, and contextualize Indigenous relationships with culture and landscape over time (Imang, 2020a). One might distinguish'knowledge' as factual data, 'belief' as religious concepts, and'tradition' as practice, but these terms are often used imprecisely and interchangeably to describe Indigenous epistemologies (Imang, 2020b).Indigenous knowledgesare conveyed formally and informally am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The successful outcome of the initiative and the challenges it faced are described in the book authored by Rodericks (2020). Duakaju and Imang (2021) undertook a qualitative study in Kalimantan, Indonesia, to study the traditional agriculture different ethnic and sub-ethnic groups. They found that swidden ("slash and burn") agricultural practices were widely practised by several ethnic groups utilising inland land and forest areas sufficiently large for farming.…”
Section: Extension Programs In Actionmentioning
confidence: 99%
“…The successful outcome of the initiative and the challenges it faced are described in the book authored by Rodericks (2020). Duakaju and Imang (2021) undertook a qualitative study in Kalimantan, Indonesia, to study the traditional agriculture different ethnic and sub-ethnic groups. They found that swidden ("slash and burn") agricultural practices were widely practised by several ethnic groups utilising inland land and forest areas sufficiently large for farming.…”
Section: Extension Programs In Actionmentioning
confidence: 99%